Tissue Expression of MLH1, PMS2, MSH2, and MSH6 Proteins and Prognostic Value of Microsatellite Instability in Wilms Tumor: Experience of 45 Cases. (11th April 2013) - Diniz, Gulden; Aktas, Safiye; Cubuk, Cankut; Ortac, Ragip; Vergin, Canan; Olgun, Nur
<x xml:space="preserve">Abstract</x> Background: Although the importance of microsatellite instability (MSI) and mismatch repair genes (MMR) is strongly established in colorectal cancer seen in the Lynch syndrome, its significance has not been fully established in Wilms tumor (WT). The aim of this study was to determine the prognostic value of MSI and MMR proteins in WT. Methods: This study included 45 pediatric cases with nephroblastoma. Protein expression was analyzed by immunohistochemistry of archival tissue sections. Real-time PCR melting analysis and fluorescence capillary electrophoresis (FCE) were performed to evaluate the MSI markers BAT25, BAT26, NR21, NR24, MONO27, penta D, and penta C in DNA extracted from tumor and normal tissues. Results: Lower levels of MSI were observed in six cases (13.3%). There were no statistically significant correlations between MSI and some clinical prognostic factors such as stage of the tumors, and survival rates. Nineteen tumors (42.2%) showed loss of protein expression of MLH1, PMS2, MSH2, or MSH6. MMR protein defects were correlated with size (P = .021), and stage (P = .019) of the tumor, and survival rates (P < .01). Similarly MSI was also correlated with the size of the tumor (P = .046). Conclusions: This study showed that a small proportion of WT might be associated with the presence of MSI, as is the case with defects of DNA mismatch repair genes in the pathogenesis of WT. However, there was no concordance with the frequency of tissue expression of MMR proteins and MSI. These findings suggest that MMR genes may play an important role in the development of WT via different pathways.